Considering maturation status and relative age in the longitudinal evaluation of junior rugby league players - Till, K.; Cobley, S.; O'Hara, J.; Cooke, C.; Chapman, C. (Scandinavian Journal of Medicine & Science in Sports, 2014)
This study longitudinally evaluated whether maturation and relative age interact with time during adolescence to differentially affect the development of anthropometric and fitness characteristics in junior rugby league players. Anthropometric and fitness characteristics of 81 junior players selected into the UK Rugby Football League's talent identification and development process were assessed over three consecutive occasions (i.e., under-13s, -14s, -15s). Players were grouped and compared in relation to maturational status (i.e., early, average, late) and relative age quartile (i.e., quartile 1). Repeated measures multivariate analysis of variance identified significant (P < 0.001) overall main effects for maturation group, relative age quartile and importantly a maturation group by time interaction. Findings showed that the early-maturing group had the greatest anthropometric characteristics and medicine ball throw across the three occasions. However, the late-maturing group increased their height (early = 5.0 cm, late = 10.3 cm), medicine ball throw and 60-m sprint (early = -0.46 s, late = -0.85 s) the most throughout the 2-year period. Early (de)selection policies currently applied in talent identification and development programs are questionable when performance-related variables are tracked longitudinally. During adolescence, maturation status alongside relative age should be considered and controlled for when assessing athlete potential for future progression.